SEED POWDER OF STRYCHNOS POTATORUM AS A NEW NATURAL EMULSIFYING AGENT - Chandra Sekhara Rao G; Sampath K.a
Stable emulsions represent an effective formulation approach for masking the bitter taste of many drugs. Due to some unwanted side effects observed recently, synthetic surfactants are facing disfavor during the formulation of emulsions. The present study was undertaken to assess the potential of the traditional medicinal plant Strychnos potatorum seed powder as a new natural emulsifying agent. Physicochemical properties of the seed powder, acacia and tragacanth were compared. Castor oil emulsions were prepared by wet-gum method, using seed powder and gum acacia at different concentrations. The physical stability of the prepared emulsions was evaluated by freeze-thaw cycling and centrifugation methods. The results were graphically represented and summarized. In the centrifugation, the lowest volumes of aqueous phase were separated for F1 and F7 emulsions. The results showed that the seed powder of S. potatorum could be utilized as a promising alternative natural emulsifying agent.